University Outreach and Local Sustainable Development: A literature review (Research, Society and Development, 2021)
Higher Education Institutions (HEIs) are the basis for building scientific and technological knowledge that will ultimately drive local development. In this context, the University Extension acts as a bridge, connecting the results of research produced within the HEIs to society demands, as well as acting as a powerful practical teaching tool, crucial for student training. The objective of this study was to carry out a literature review on the historical panorama of University Extension, both nationally and worldwide, as well as on the evolution of the concepts of economic, sustainable and local development, to understand the potential of University Extension as promoter of Sustainable Local Development. For this purpose, bibliographic and documentary research was carried out. From this research, we conclude that through direct action on educational, economic, social, environmental and cultural issues in the localities and regions where Higher Education Institutions are located, the University Extension represents an important driving force for local development, building, in partnership with the benefited communities, innovative solutions capable of solving or mitigating the problems afflicting them.